Choosing Between the One-Way or Two-Way Street: An Exploration of Relationship Promotion by Professional Athletes on Twitter. (March 2014) - Frederick, Evan; Lim, Choong Hoon; Clavio, Galen; Pedersen, Paul M.; Burch, Lauren M.
The purpose of this study was to explore the relationships promoted by professional athletes on Twitter utilizing the theoretical framework of parasocial interaction (PSI). Specifically, this study was a content analysis that examined professional athlete tweets in order to determine whether they predominately promoted social or parasocial relationships. The study also explored with whom athletes were engaging in social interaction as well as the topic of each tweet. The data revealed that professional athletes promoted both parasocial and social relationships equally. When they chose to be social, athletes were communicating with lay people and other professional and college athletes. Most athlete tweets were either general statements or insights into their personal lives. The implications of these and other findings will be discussed further.